Association of seizure co-morbidity with early hospital readmission among traumatic brain injury patients. (14th October 2020) - Kwon, Michelle; Lekoubou, Alain; Bishu, Kinfe G.; Ovbiagele, Bruce
ABSTRACT: Objective: To assess the frequency of seizure co-morbidity and its independent association with 30-day readmission rate among patients hospitalized with traumatic brain injury (TBI) in the United States. Methods: The data source was the 2014 Nationwide Readmission Database. We included adults (Age ≥18 years) with a primary discharge diagnosis of TBI, identified using the International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) codes 800.0, 801.9, 803.0, 804.9, 850.0–854.1, and 959.01. Seizures were diagnosed using the ICD-9-CM codes of 345.x and 780.39. Overall and across pre-specified groups 30-readmission rate was computed. Logistic regression analysis was used to identify independent predictors of 30-day readmission. Results: Among 76, 062 unweighted adults discharged with a diagnosis of TBI, 7, 776 (10.14%) had a secondary discharge diagnosis of seizures.A total of 1, 751 (2.3%) patients with a primary discharge diagnosis of TBI were readmitted within 30 days. On multivariate logistic analysis, patients discharged with a secondary diagnosis of seizures were 18% more likely to be readmitted within 30 days compared to those without seizures (OR 1.18, 95% CI: 1.01–1.39, P = .42). Conclusion: One in 10 patients hospitalized with TBI in the US have a co-morbid seizure disorder. Seizure co-morbidity conferred 18% greater odds of being readmitted within 30 days.